IMPROVE: a feature model to predict neoepitope immunogenicity through broad-scale validation of T-cell recognition - Borch, Annie; Carri, Ibel; Reynisson, Birkir; Alvarez, Heli M. Garcia; Munk, Kamilla K.; Montemurro, Alessandro; Kristensen, Nikolaj Pagh; Tvingsholm, Siri A.; Holm, Jeppe Sejerø; Heeke, Christina; Moss, Keith Henry; Hansen, Ulla Kring; et al. (Frontiers in Immunology, 2024)
Mutation-derived neoantigens are critical targets for tumor rejection in cancer immunotherapy, and better tools for neoepitope identification and prediction are needed to improve neoepitope targeting strategies. Computational tools have enabled the identification of patient-specific neoantigen candidates from sequencing data, but limited data availability has hindered their capacity to predict which of the many neoepitopes will most likely give rise to T cell recognition.To address this, we make use of experimentally validated T cell recognition towards 17,500 neoepitope candidates, with 469 being T cell recognized, across 70 cancer patients undergoing immunotherapy. We evaluated 27 neoepitope characteristics, and created a random forest model, IMPROVE, to predict neoepitope immunogenicity. The presence of hydrophobic and aromatic residues in the peptide binding core were the most important features for predicting neoepitope immunogenicity. Overall, IMPROVE was found to significantly advance the identification of neoepitopes compared to other current methods.